Arterial Stiffness and Cerebral Small Vessel Disease - Zhai, Fei-Fei; Ye, Yi-Cong; Chen, Si-Yu; Ding, Fa-Ming; Han, Fei; Yang, Xing-Lin; Wang, Quan; Zhou, Li-Xin; Ni, Jun; Yao, Ming; Li, Ming-Li; Jin, Zheng-Yu; et al. (Frontiers in Neurology, 2018)
Background and objective Studies on relations between arterial stiffness and full spectrum of radiological features of cerebral small vessel disease (CSVD) are scarce. We aim to investigate the association of arterial stiffness with lacunes, white matter hyperintensities (WMH), microbleeds (CMBs), dilated perivascular spaces (PVS), and brain atrophy in a community-based sample. Methods A total of 953 participants (55.7±9.4 years) who underwent brachial-ankle pulse wave velocity (baPWV) and brain magnetic resonance imaging were included. Lacunes, CMBs, and PVS were visually rated. Brain structure and WMH were automatically segmented. Brain parenchyma fraction (BPF), a surrogate index of brain atrophy, was calculated as a ratio of brain parenchyma volume to total intracranial volume. Multivariable logistic and linear regressions were used to investigate the associations between baPWV and CSVD. Subsequently, we explored these associations in strata of age. Results Increased baPWV was associated with severe PVS in white matter (OR, 1.10; 95%CI, 1.03–1.17; p=0.007), strictly lobar CMBs (OR, 1.11; 95%CI, 1.01–1.22; p=0.035), larger WMH volume (β, 0.08; 95%CI, 0.04–0.11; p<0.001), and lower BPF (β, -0.08; 95%CI, -0.14– -0.02; p=0.013), but not with lacunes. WMH volume mediated the relation between baPWV and BPF. In age subgroup analysis, the association of baPWV with PVS in white matter was stronger among those aged <55 years, whereas the association with brain atrophy was more prominent among those aged ≥55 years. Increased baPWV was associated with larger WMH volume in both younger and older individuals. Conclusions Increased arterial stiffness was associated with most of imaging markers of CSVD, including PVS in white matter, larger WMH volume, strictly lobar CMBs, and brain atrophy, but not lacunes. The mechanisms underlying these associations and their potential clinical significances warrant further investigations.